Antigen-capture enzyme-linked immunosorbent assay using monoclonal antibody for detection of bluetongue virus antigen An - Sendow, Indrawati (Indonesian Animal Sciences Society, 1998)
antigen-capture enzyme-linked immunosorbent assay (ELISA) using a specific anti-bluetongue virus group was applied to detect bluetongue viral antigen . The test was specific for bluetongue viruses and did not detect the closely related epizootic haemorrhagic disease of deer viruses (EHDV) and other orbiviruses . It was easy to perform and could be established in laboratories which have simple facilities . The antigen-capture ELISA technique is an alternative method to agar gel immunodiffusion and immuno-dot blotting tests to detect bluetongue antigen in infected tissues, Vero cells, Aedes albopictus cells and BHK-21 cell cultures . Â Keywords : ELISA, monoclonal antibody, antigen detection, BT